A incompletude além da matemática: impactos culturais do Teorema de Gödel no século XX - Wagner Lannes (2009)
In 1930, the Austrian logician mathematician Kurt Gödel proved that if has not contradictories theorems in a formal system contained the arithmetic hence exists propositions in this system that cant be proved nor refuted. Its corollary tell us that the own system cant prove the existence of this contradictories theorems. The meaning on this theorem and its corollary to mathematics and to logic, and its philosophical conclusions and critics of the abuses about its uses in non mathematicians circles are issues sufficiently debated on scientific literature, but the historical movement of ownership of Gödels results of the scientific community of non mathematicians is a problem worthy of reflection and one of the main contributions sought in this work.